Cinemasophia in John de Rantau's Denias : Senandung di Atas Awan / Rohani Md. Yousoff - Md. Yousoff, Rohani (UPENA, 2008)
Through his film John de Rantau has evoked wisdom through the visuals which gives a deeper meaning to the need of education. These are visualized through archetypical, traditional and modern symbols which arouse long-forgotten instincts and much neglected links with nature. The visuals used by de Rantau are treasures that please the eyes and go deep into the heart. For every deprived child, there is hope; for every lost soul there is home. This film is inspirational, done with a sensitivity which goes beyond the realm of reality; for the reality is not the present but in the search of knowledge of the Truth, which is what Denias finds. The Truth is there to be discovered but not without its challenges and hardships as faced by young Denias in his desire to be educated. For Denias it all begins with belief in his 'self'.